Desempenho reprodutivo de varrões e matrizes suínas de diferentes linhagens durante as estações do ano - Zanardo, João Antonio (2016)
The industrial Brazilian pig farming despite of the constant advance in the genetic improvement, nutrition, and in handling, seasonality problems occur in the production of weaned piglet, mainly due to the stations of the year that can impact directly in the profitability. These problems can be deepen due to breed and line of decent used in Brazil are all source from tempered weather countries. To the pig farmer it's difficult to determine the relations between indoor temperature of the barns, relative humidity of the air and top thermal amplitude which can provide good reproductive rates for the boars and arrays lodged in conventional barns. The lack research to production of environmental indices of easy interpretation to pigs, which are not dependent of complicated handling machines and also which are not expensive is considered as a negative factor from the producers. the objective os this experiment is evaluate the effects of the stations of the year over the reproductive performance of the boars Agroceres PIC 425, Agroceres PIC 337 and D.B. Dambred LM 6200, and of arrays Agroceres Canborough 22, Penarlan Naima e DB90 Danbred, in addition develop an environmental index with easy interpretation and use to the pig farmers of the region of Uberlândia - MG, using the maxim temperatures, rainfall monthly accumulated and of the thermal amplitude of the barn. The features rated during the stations of the years 2013 and 2014 were the volume and spermatic quality of the boars and the mainly reproductive indexes of the arrays as the total number of piglets born alive and total number of weaned piglets/ array/ parturition. The station of the year which had the worst results in the reproductive feature of the boars and arrays was the spring. Boars from different line of decent are sensitive to the effects of stress of the heat of spring causing lowest volume, concentration and problems in the spermatic morphology (p<0,05). The spring prejudice the reproductive indexes of arrays from different line of decent (p<0,05) and the pig farmers of Uberlândia are subjected to operating losses and income evasion due to the thermal stress in the reproduction that added can reach $150.000,00 annual for each 1000 arrays lodged/year.